IMPLEMENTASI AKUNTANSI SEKTOR PUBLIK DALAM PELAPORAN KEUANGAN PEMERINTAH: STUDI LITERATUR - Fitri Adil Nilamsari; Muhammad Vryzas Fadillah; Bening Diana Putri (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
The purpose of the study was to determine whether the implementation of public sector accounting based on the conceptual framework affects the quality of government financial reports. This research uses a qualitative descriptive method, which involves identification, evaluation, and interpretation of previous research results. The results showed that the conceptual framework is not only a reference in the preparation of accounting standards, but also directs the implementation of accounting standards that support the improvement of the quality of financial statements despite several obstacles such as human resource competencies and infrastructure..